2010
DOI: 10.1038/nri2691
|View full text |Cite
|
Sign up to set email alerts
|

The IL-1 family: regulators of immunity

Abstract: Over recent years it has become increasingly clear that innate immune responses can shape the adaptive immune response. Among the most potent molecules of the innate immune system are the interleukin-1 (IL-1) family members. These evolutionarily ancient cytokines are made by and act on innate immune cells to influence their survival and function. In addition, they act directly on lymphocytes to reinforce certain adaptive immune responses. This Review provides an overview of both the long-established and more r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
1,010
2
21

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,195 publications
(1,050 citation statements)
references
References 177 publications
17
1,010
2
21
Order By: Relevance
“…We next investigated whether other members of the IL-1 family such as IL-1b and IL-18 (ref. 37) are produced upon treatment with Aldara. It was shown that IMQ activates the inflammasome in murine peritoneal macrophages, 38 but such evidence is lacking for keratinocytes.…”
Section: Article Nature Communications | Doi: 101038/ncomms2566mentioning
confidence: 99%
“…We next investigated whether other members of the IL-1 family such as IL-1b and IL-18 (ref. 37) are produced upon treatment with Aldara. It was shown that IMQ activates the inflammasome in murine peritoneal macrophages, 38 but such evidence is lacking for keratinocytes.…”
Section: Article Nature Communications | Doi: 101038/ncomms2566mentioning
confidence: 99%
“…IL-33 is a member of IL-1 family [9][10][11]. Like IL-1b or IL-18, IL-33 is synthesized as a precursor and can be cleaved by caspase-1 and 3 but the cleavage products are biologically less active than the precursor [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Th2 cells have been shown to play a predominant role in allergic asthma and Th2 cytokines, such as IL-4, IL-5 and IL-13, exacerbate disease severity [3,4]. IL-33, the recently discovered Th2 cytokine, is found at high levels in the plasma of asthmatic patients [5,6] and in the lungs of mice during experimental allergic asthma [7,8].IL-33 is a member of IL-1 family [9][10][11]. Like IL-1b or IL-18, IL-33 is synthesized as a precursor and can be cleaved by caspase-1 and 3 but the cleavage products are biologically less active than the precursor [12,13].…”
mentioning
confidence: 99%
“…The IL-1 cytokine family plays a key role in the regulation of inflammation and immunity [44,45]. It has been reported that IL-1β may promote the expansion of memory T cells and upregulate antigen-specific effector T-cell functions [46,47].…”
Section: Discussionmentioning
confidence: 99%
“…This effect was detectable when IL-1β was added at the beginning of the culture, thus indicating an early effect on CD34 + cell differentiation. In line with this hypothesis, molecular analysis indicated that in the presence of IL-1β, an increase of ID2 and E4BP4 mRNA relative expression could be observed in cell precursors as early as 4 days of cultures.The IL-1 cytokine family plays a key role in the regulation of inflammation and immunity [44,45]. It has been reported that IL-1β may promote the expansion of memory T cells and upregulate antigen-specific effector T-cell functions [46,47].…”
mentioning
confidence: 99%